Study about Fabrication and Evaluation of Different Thermal Barrier Coating Systems - Mukherjee, Poulomi; Roy, Pallabi; Ghosh, Sumana (Research Developments in Science and Technology Vol. 1, 2022)
A new thermal barrier coating (TBC) system comprised of 8-YSZ top coat, glass-ceramic bond coat and nimonic supper alloy substrate was fabricated by using vitreous enameling and atmospheric plasma spraying (APS) techniques. Conventional TBC system consisting of 8-YSZ top coat, NiCoCrAlY bond coat and nimonic supper alloy substrate was formed by APS technique. The objective of the present study was to compare the thermal cyclic performance of glass-ceramic bonded TBC systems with that of the conventional TBC systems. Both the TBC systems were characterized by X-ray diffraction analysis for phase identification, scanning electron microscopy for microstructural examination, energy dispersive X-ray analysis for elemental composition determination and Vickers hardness tester for hardness evaluation. Additionally, both TBC systems were subjected to thermal cycling tests at 1000oC for 250 h by air quenching and water quenching methods. More gradual transition in microhardness values were observed for glass-ceramic bond coated TBC system compared to those for conventional TBC system, which indicated more reliable performance in case of the new TBC system. Thermal cycling carried out at 1000oC showed the stability of both TBC systems under air quenching tests for 250 cycles whereas coating spallation was observed in case of water quenching tests for 150 cycles for both TBC systems. Further, significant oxidative weight gain was noted for conventional TBC system, which was not observed for the new TBC system.